Changes in oxidative stress from tracheal aspirates sampled during chest physical therapy in hospitalized intubated infant patients with pneumonia and secretion retention - Jirakrit Leelarungrayub (2018)
© 2016 Leelarungrayub et al. Objective: This study aimed to show the changes in oxidative stress and clinical condition from either chest physical therapy (CPT) or CPT with aerosol treatment in infant patients with pneumonia. Methods: From 52 intubated patients, three groups were composed: groups A, B, and C comprising 21 patients aged 5.3±0.6 months (CPT program), 20 patients aged 5.6±0.7 months (aerosol treatment before CPT program), and eleven patients aged 5.0±0.35 months (control), respectively. CPT was composed of manual percussion and vibration before suction in a specific position for draining secretion and re-expanding collapsed lungs. Groups A and B received three sessions of treatment three times daily for 6 days, when tracheal aspirates were collected for evaluating oxidative stress markers for the thiol group: vitamin E, thiobarbituric acid reactive substances-malondialdehyde, and hyarulonan. Furthermore, lung injury score and oxygenation index (PvO2/FiO2ratio) were recorded daily. Results: All parameters in group C did not change statistically during study. The thiol group increased significantly in group A after day 4, and increased significantly on days 3 and 6 when compared to day 1 in group B. Vitamin E levels increased significantly on days 3, 5, and 6 in group A, and days 3, 4, and 6 in group B, when compared to day 1. Whereas, the thiobarbituric acid reactive substances-malondialdehyde adduct showed a significant reduction after day 4 in groups A and B, when compared to day 1. Hyarulonan levels showed a significant reduction after day 3 in group A and on day 2 in group B. In addition, lung injury score decreased slightly and nonsignificantly in groups A and B, whereas the oxygenation index increased significantly after day 4 in group A and on day 6 in group B. Conclusion: These preliminary results suggest that CPT with or without aerosol treatment possibly reduces oxidative stress and enhances oxygenation status in infant patients.